Temporal evolution of strategic narratives: Chinese TikTok propaganda and the South China Sea conflict - Ronel Jhon Lumor Guarte; Kehm Angel Socayre; Sidik Jatmika; Surwandono Surwandono (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2025)
Despite extensive research on social media influence, a significant gap exists in understanding how audiences interpret and engage with Chinese propaganda on short-form video platforms, particularly regarding territorial disputes. This study examines the temporal evolution of strategic narratives in Chinese TikTok propaganda related to the South China Sea conflict, integrating Walton's propaganda framework with Strategic Narrative Theory. A quantitative survey approach employed 100 university students from Universitas Muhammadiyah Yogyakarta who evaluated five Chinese state-controlled TikTok videos using surveys based on Walton's ten propaganda characteristics, with temporal pattern analysis examining strategic narrative evolution across the video sequence. Statistical analysis revealed three distinct strategic narrative types: (1) core narratives maintaining consistency across videos (PC4, PC6, PC8), (2) adaptive narratives demonstrating systematic learning and optimization (PC10), and (3) experimental narratives testing alternative approaches (PC1, PC7). The findings demonstrate that Chinese propaganda operates through sophisticated portfolio management strategies combining narrative stability with dynamic optimization mechanisms, indicating a mature understanding of digital audience psychology and cross-cultural influence effectiveness. This research advances strategic communication theory by providing empirical evidence that contemporary digital propaganda functions as evolving strategic narrative systems rather than static content, requiring analytical frameworks capable of capturing dynamic communication processes in competitive information environments.